Editorial: an argument for low‐dose thiopurine allopurinol combination use as first‐line therapy in inflammatory bowel disease. Issue 1 (7th June 2018) - Ansari, A. R.; Aziz, A.
Abstract : Linked Content This article is linked to Friedman et al and Friedman and Sparrow papers. To view these articles visithttps://doi.org/10.1111/apt.14571 andhttps://doi.org/10.1111/apt.14798 .